A Study of The Relationship Between Macro Economic Factors and The Indian Stock Market - Mittal, Rohit (2010)
This dissertation is a study on the relationship of various macro economic variables and the Indian stock market. The study aims to show the impact of macro economic variables on the capital market. To conduct the study we have taken Bombay Stock Exchange’s index – SENSEX and National Stock Exchange’s index – S&P CNX Nifty as the benchmark of the Indian stock market. To get a broader insight we have taken various macro economic indicators like Wholesale Price Index, Money Stock represented by M3, Index of Industrial Production, Fiscal Deficit of the Central Government, Net investment by Foreign Institutional Investors, INR/USD Exchange Rate and Foreign Exchange Reserve. The research is conducted over monthly data of ten years period (2000-2010). There is a significant relationship between the economy and the stock market in the long-term. However in the short-term macro economic variables failed to show any significant relationship with the stock market.